Transaminase and phosphatase activity of blood and seminal plasma in breeding bulls of different breeds - DHAMI, A J; SHELKE, VINAYA B; VIRANI, A C; KAVANI, F S; DAVE, R R (The Indian Journal of Animal Reproduction, 2023)
The normal profile of blood plasma and seminal plasma transaminases and phosphatases was studiedtwice at monthly interval in 37 breeding bulls ofGir, Holstein Friesian, Jersey, Crossbred and Jafarabadi breeds.The differences between breeds were significant (P
Keywords: Transaminases; phosphatases; blood plasma; seminal plasma; breeding bulls